2008
DOI: 10.5194/angeo-26-3225-2008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ECMWF analyses with GPS radio occultations from CHAMP

Abstract: Abstract.A climatological validation of the 6-hourly operational ECMWF troposphere and lower stratosphere temperatures as well as geopotential heights between 1000 and 10 hPa is performed using the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…They found that the difference introduced by the application of vertical instead of horizontal filtering exceeds the differences between data sets applying the same method significantly. Schmidt et al (2016) confirmed that different techniques (in particular vertical spectral filtering versus horizontal S-transform analysis) have a large impact on the global gravity wave activity results, especially comparing gravity wave potential energy densities and gravity wave momentum flux estimates. In addition, they strongly recommend to use horizontal filtering for the detrending.…”
Section: Introductionmentioning
confidence: 61%
“…They found that the difference introduced by the application of vertical instead of horizontal filtering exceeds the differences between data sets applying the same method significantly. Schmidt et al (2016) confirmed that different techniques (in particular vertical spectral filtering versus horizontal S-transform analysis) have a large impact on the global gravity wave activity results, especially comparing gravity wave potential energy densities and gravity wave momentum flux estimates. In addition, they strongly recommend to use horizontal filtering for the detrending.…”
Section: Introductionmentioning
confidence: 61%
“…The accuracy of the RO temperature measurements could be broadly documented. In the past, several comparison studies between GPS RO data and radiosondes as well as cross validations with other satellite sensors have been performed [ Hajj et al , 2004; Kuo et al , 2005; Steiner et al , 2007; Gobiet et al , 2007; Schmidt et al , 2008; Heise et al , 2008]. Special comparisons of tropopause parameters between CHAMP and ECMWF (European Centre for Medium‐Range Weather Forecasts) or NCEP (National Centers for Environmental Prediction) analyses are given by, for example, Borsche et al [2007] and Schmidt et al [2004, 2005b].…”
Section: Introductionmentioning
confidence: 99%
“…Both AIRS retrievals—infrared‐only and combined infrared and microwave—contain a large error in the annual cycle of temperature poleward of 60°S in the stratosphere, alternating in sign approximately every scale‐height. The error is ≈3 K. Such behavior has been observed in comparisons of GPS RO temperature climatologies with atmospheric analyses that are strongly informed by nadir radiance data (Bormann & Healy, ; Foelsche et al, ; Gobiet et al, ; Schmidt et al, ). The error could not be discerned in the radiance data itself, and thus it was identified as a null‐space error in the atmospheric analyses.…”
Section: Conclusion and Discussionmentioning
confidence: 61%